2021
DOI: 10.1097/yco.0000000000000702
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenia during the COVID-19 pandemic

Abstract: Purpose of reviewThe coronavirus disease 19 (COVID-19) pandemic is having a critical impact on healthcare systems across the world, as well as on mental health in the general population; however, evidence regarding the impact of the COVID-19 pandemic on people living with schizophrenia and on the onset of psychotic symptoms is currently emerging. Recent findingsPeople living with schizophrenia are at an increased risk of COVID-19 and present worse COVID-19related outcomes, including mortality. They show low le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 66 publications
3
46
0
1
Order By: Relevance
“…Many of these factors are found in mental health patients and especially those suffering from schizophrenia. 3,4 It is reported that mechanical ventilation, admission to an intensive care unit and death are more likely adverse outcomes among COVID-19 patients who are also diagnosed with mental disorders. 5 Therefore, it would be very interesting to elucidate whether a) patients with schizophrenia are more frequently infected with SARS-CoV-2, and b) schizophrenia is associated with higher mortality from COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these factors are found in mental health patients and especially those suffering from schizophrenia. 3,4 It is reported that mechanical ventilation, admission to an intensive care unit and death are more likely adverse outcomes among COVID-19 patients who are also diagnosed with mental disorders. 5 Therefore, it would be very interesting to elucidate whether a) patients with schizophrenia are more frequently infected with SARS-CoV-2, and b) schizophrenia is associated with higher mortality from COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…조현병 환자는 코로나19 감염에 취약해 일반인에 비해 높 은 감염 위험성이 보고된다. 8,13,14) 미국의 전자의무기록을 분석 한 연구에서는 조현병 환자의 코로나19 감염율은 대조군에 비 해 약 9.9배 높았고, 인구사회학적 요인과 신체건강상태를 통 제하고서도 7.3배 높았다. 15,17,24,25) 항정신병약물을 복용 중인 경우 폐렴 발생 위험성이 증가할 수 있다고 보고되는데, 약물로 인한 진정 효과, 연하 곤란, 침 과다분비, 후두 및 인두 근력 약화 등이 원인이 될 수 있다.…”
Section: 조현병 환자의 코로나19 감염 취약성unclassified
“…Studies conducted in the first phases of the pandemic reported that schizophrenia patients showed low levels of information and concern regarding contagion, an increased risk of SARS-CoV-2 infection, and worse COVID-19-related outcomes, including mortality. The severity of psychotic symptoms, however, was substantially stable and subjective well-being did not worsen significantly, probably as a result of the autistic features and tendency towards isolation that frequently characterize this population ( Barlati et al, 2021 ).…”
mentioning
confidence: 92%